Anti-wetting surfaces with self-healing property: Fabrication strategy and application - Jiang, Shuyue; Zhang, Haifeng; Liu, Xiaowei (Journal of industrial and engineering chemistry (Seoul, Korea), 2023)
[Display omitted] Anti-wetting surfaces (superhydrophobic and slippery liquid-infused surfaces) are of considerable current interest due to their unique abilities, addressing many vital technical problems such as icing of glass, corrosion of metal, surface contamination of fabric and treatment of oily wastewater. But the unsustainability of anti-wetting surfaces has severely hindered their industrial applications. Self-healing inspired from plants and human skins can effectively enhance the longevity and durability of anti-wetting surfaces. However, the comprehensive investigation concerning the fabrication strategies of self-healing anti-wetting surfaces from the point of substrates is yet not obtained up to date. In this review, we summarized the fabrication strategies of self-healing anti-wetting surfaces on glass, metals, fabrics and polymers. Then the application of self-healing anti-wetting surfaces in the fields of anti-icing, anti-corrosion, anti-fouling and oil–water separation were comprehensively reviewed in detail. Finally, great challenges and further perspectives on the application of self-healing anti-wetting surfaces are presented.